Meta-Analysis of the Impact of Problem-Based Learning on High School Students' Critical Thinking Abilities in Biology Education - Ummi Kalsum Harahap; Ganda Hijrah Selaras; Ardi Ardi (Journal of Digital Learning and Education, 2023)
Every individual should possess the ability to think critically, making it imperative to foster this process starting from school. The purpose of this research is to analyze previously published studies to conclude on the success of the problem-based learning model in enhancing high school students' critical thinking skills in biology education. The research methodology employed is meta-analysis, where the researcher combines the outcomes of prior studies to obtain a comprehensive overview of the success of the problem-based learning model in enhancing critical thinking skills among high school students in biology education. The research findings indicate that the implementation of the problem-based learning model in biology education at the high school level can indeed enhance students' critical thinking abilities. This is evident from the comparison between pretest and posttest results, revealing an average increase of 0.17%. While this falls within the weak effect category, it still demonstrates a positive impact of Problem-Based Learning on students' critical thinking skills. The utilization of the Problem-Based Learning model contributes significantly to the cultivation of students' critical thinking skills in the context of biology education.